Case Report: A rare case of bilateral middle ear tophaceous gout - Camurdan, Aybige; Riemann, Conrad; Brasch, Frank; Todt, Ingo (Frontiers in Surgery, 2024)
Introduction Hypacusia can be caused by various etiologies; however, hearing loss attributed to gouty tophi remains a rare occurrence. This case report presents, for the first time, a bilateral gouty tophi causing hearing impairment. Case presentation This report describes a case study involving an 83-year-old Caucasian female patient who presented symptoms of hypacusia, pruritus, and a sensation of pressure in her right ear. A computed tomography scan revealed the presence of non-homogeneous calcified structures in both ears. Following a comprehensive assessment that included pure-tone audiometry and a thorough evaluation of the patient's clinical complaints, a tympanoplasty procedure was initially performed on the right ear. Pathological analysis revealed the presence of gouty tophi. After surgical removal of the tophus, a notable improvement in the patient's hearing threshold was observed. Four months later, a similar surgical intervention was performed on the contralateral ear, achieving a similar positive outcome. The substantial postoperative decrease of bone conduction indicates an inner ear affection by the gout tophi. Conclusion Gout tophus in both ears is a very rare but possible cause of hypacusia, even in the absence of a pre-existing diagnosis of systemic gout disease. We report a case of gout tophi in both ears as a rare cause of hearing loss.